Amplification of the epidermal-growth-factor-receptor gene correlates with different growth behaviour in human glioblastoma - Schlegel, Jürgen; Merdes, Annette Ruth; Stumm, Gabi; Albert, Friedrich; Forsting, Michael; Hynes, Nancy; Kiessling, Marika (International journal of cancer, 1994)
The objective of our study was to determine the frequency of EGF-receptor-gene rearrangement in relation to tumour-growth behaviour in an unselected group of glioma patients. We investigated 73 glial tumours with different grades of malignancy (17 low-grade gliomas, 14 anaplastic variants, and 42 GBM) by Southern analysis, reverse transcriptase PCR (RT-PCR) amplification of mRNA, and Western analysis. An amplification of the EGF-receptor gene was present in 19/42 GBM but in only I anaplastic astrocytoma. By RT-PCR, 4/19 GBM with gene amplification showed a specific amino-terminal aberrant splice mutation of 801 bp in addition to undeleted mRNA. By Western analysis, 27/42 GBM showed expression of the EGF-receptor protein. Protein levels, however, varied among individual tumours. Four GBM containing an aberrant splice mutation exhibited an immunoreactive protein of 130 kDa MW in addition to the normal EGF-receptor protein p170. All GBM patients underwent surgery followed by a standard course of radiotherapy. Neuroradiological follow-up in 31/42 GBM patients consisted of bimonthly MRJ examinations. There was a statistically significant difference in the mean latency period until tumour regrowth of patients suffering from GBM with and without EGF-receptor-gene amplification (9 weeks vs. 32 weeks). Our data indicate more rapid tumour regrowth kinetics of GBM with amplified EGF receptor genes in vivo. © 1994 Wiley-Liss, Inc.